Detection of Salmonella in Poultry Using Conventional Culture Methods and Polymerase Chain Reaction Technique - Kammon, Abdoal Wahab M. M. Masud (2003)
A study was carried out to evaluate three culture media and PCR for the detection of Salmonella spp. to improve Salmonella monitoring program. A total of 109 samples were collected from two farms. Sixty four samples were collected from farm A. These included 16 cloacal swabs collected from broilers before slaughtering, 18 intestinal swabs and 20 caecal swabs collected from broilers after evisceration, and 10 cloacal swabs collected from village chickens. Forty five samples were collected from farm B, which included 15 cloacal swabs from each of village chickens, turkeys, and guinea fowls. Samples were pre-enriched in BPW and investigated by plating them on XLT4 agar after enrichment in selenite cystine broth, BPLS agar after enrichment in Rappaport-Vasilliadis broth, and DIASALM directly after pre-enric hment in BPW. Suspected positive colonies were confirmed biochemically and serologically. DIASALM and BPLS agar were comparatively evaluated against XLT4 agar as the "gold standard" using Kappa statistic to determine the level of agreement between them. A total of 27 (24.77%) Salmonella were detected from the 109 samples. Isolation rates for XLT4, DIASALM, and BPLS were 20.20% (22 out of 109), 17.43% (19 out of 109), and 13.8% (15 out of 109), respectively. The sensitivity and agreement (Kappa statistic) with the "gold standard" for each evaluated detection method were: 70.4% and 0.69 (substantial) for DIASALM and 55.56% and 0.58 (mode rate) for BPLS. For the detection of Salmonella spp. by PCR, bacterial chromosomal DNA was extracted by boiling. Amplicons (429 bp) and (284 bp) derived from primers to the genomic random fragment (primers ST11 and ST15) and invA genes (primers 139 and 141) respectively, were confirmed as Salmonella specific on ethidium bromide-stained agarose gels. Using PCR assay Salmonella was detected 24% (13 out of 54) and 13% (7 out of 54) in broilers in farm A using primers ST11-ST15 and 139-141, respectively. Poultry species in farm B were negative for Salmonella by PCR. A specific primer was used for the detection of Salmonella enteritidis. None of Salmonella detected was Salmonella enteritidis. This study concluded that XLT4 agar is the most sensitive medium and is very specific for the isolation of Salmonella from chicken feces. DIASALM is a good medium for the isolation of Salmonella. The inability of PCR to successfully detect Salmonella specific products from all the samples that were positive for isolation is not clear. However, this would be partly explained by the presence of inhibitor factors in the DNA preparations. In addition, the primer set ST11-ST15 used in this study has not before been tested on cloacal swabs and fecal samples from poultry. Perhaps, with improved DNA extraction method may overcome the inhibitory problem and also low yield of DNA. PCR should be used together with cultivation for the detection of Salmonella especially when the serovar is to be determined.